MAL PELAYANAN PUBLIK DI KABUPATEN KUBU RAYA - Riska Septia Sari; Muhammad Ridha Alhamdani; Jawas Dwijo Putro (JMARS: Jurnal Mosaik Arsitektur, 2022)
Public services are activities service carried out by the organizers as an effort to fulfill public needs, that are profitable in a group and offer satisfaction even though the results are not bound by a physical product. Kubu Raya is a district located in the West Kalimantan province with a vast areas of  6.985,20 km² and a population of 522.174 persons. Every district community of Kubu Raya requieres a public services that provide service facilities for population administrations or permits and other documents. The public services provided by the District of Kubu Raya are various and are offer by their resepective organizer. Most of the time, the sevices needed by the population are located in different places of the district, this forces the person to make multiple different trip to multiple location while carying all the documents. The current organization isn’t effective and consume the time and the satisfaction of the user. Therefore, a place that regroupe most of the public services in one or in a near location need to created. A Public Service Mall can be build to regroupe the services, the close building is composed of all the services that can facilitate the distribution and or exchange of goods or sevices for the user. A Public Service Mall will help the user to enjoy and have acces to all the services in one location, this will be more efficient in the time management and will increase the satisafaction of the user.